Transcriptional Regulation of Epidermal Barrier Formation - Bhandari, Ambica (2011)
The mammalian epidermis is a self-renewing stratified squamous epithelium. Its basal cell layer contains proliferating keratinocytes that exit the cell cycle when they move into the suprabasal compartment. These cells activate a gene differentiation program aimed at building a protective epidermal barrier as they move toward the surface, successively going through the spinous and granular layers. At the completion of this process, the keratinocytes become enucleated and form the cornified layer, the surface layer of the skin. The highly cross-linked protein–lipid envelope and extracellular lipids in the cornified layer along with cell–cell adhesions in the granular layer are required for an effective epidermal barrier. Transcriptional mechanisms are critical for the formation of the epidermal barrier, and in this chapter, we describe methods to evaluate the role of a transcription factor (TF) in epidermal differentiation. To identify direct target genes of a TF, we propose a combination of bioinformatics and experimental approaches. The ultimate goal of these approaches is to understand the mechanisms whereby a TF regulates epidermal barrier formation.